Does the State Fail to Protect Defendant Rights in the Criminal Justice Process? A Case in Kosovo - Adelina Rakaj; Armend Podvorica (Sriwijaya Law Review, 2020)
The Republic of Kosovo is a new state that declared independence in 2008 and adopted its modern constitution also in 2008, where during twelve years the state has created a very advanced constitutional and legal system in terms of protection of freedoms and human rights in general. Also, in its legal system, Kosovo has built important mechanisms aimed at protecting the position of the defendant during criminal proceedings. Although Kosovo has established constitutional and legal guarantees for the protection of the rights of the defendant in the criminal process, the situation in practice is not satisfactory. The various data and reports reflected in this paper show that Kosovo has failed to meet the rights of the defendant and failed to protect these rights. Even this situation has continued continuously. What is disappointing about the defence of the defendant's rights is the fact that the regular courts have been careless, in enforcing the constitutional standards for the protection of the defendant's rights. In several cases, the courts have even failed to protect these rights. Kosovo's Constitutional Court is the only subject that has compensated, to some extent, the protection of the rights of the defendant. The paper reflects the practical situation in how much Kosovo has managed to apply and protect in practice the constitutional and legal guarantees offered by its legal system.